Determination of Fractional Chromatic Numbers in the Operation of Adding Two Different Graphs: Penentuan Bilangan Kromatik Fraksional pada Operasi Penjumlahan Dua Graf berbeda - Junianto Sesa; Siswanto Siswanto (Jurnal Matematika, Statistika dan Komputasi, 2022)
The development of graph theory has provided many new pieces of knowledge, one of them is graph color. Where the application is spread in various fields such as the coding index theory. Fractional coloring is multiple coloring at points with different colors where the adjoining point has a different color. The operation in the graph is known as the sum operation. Point coloring can be applied to graphs where the result of operations is from several special graphs. In this case, the graph summation results of the path graph and the cycle graph will produce the same fractional chromatic number as the sum of the fractional chromatic numbers of each graph before it is operated.